Unravelling salt stress in plants through proteomics - Hakeem, Khalid Rehman; Chandna, Ruby; Ul Rehman, Reiaz; Tahir, Inayatullah; Muhammad Sabir,; Muhammad Iqbal, (Springer, 2013)
Plants like other organisms are mostly under the threat of various stresses (both biotic as well as abiotic). Being sessile, plants lack the mechanisms to flee from these unfavourable situations. The development of exclusive and complicated responses to these environmental stresses in plants has fostered through evolution. Such alterations can influence plant growth, production and productivity in agriculture, plant nutritional potential and metabolic profile. Hence, plant abiotic stress has always been a matter of concern for the world economy and maintenance of human life on earth. Salinity stress, being one of the main abiotic stresses, may bring the morphological, anatomical, and physiological changes in plants. Distributed in both irrigated and non-irrigated areas of the world, around 6% of the world’s total land area is affected by salt stress. So, it is a major concern to adopt the strategies against this great challenge by unravelling the mechanisms to overcome salt stress. In order to meet the challenges for biotechnological improvement of crop productivity; various steps involving genes, transcripts, proteins and metabolites, controlling the stress resistance and/or architecture of crop plants in a wide array of environments needed to be recognized. Proteomics, the protein complement of genome, these days is one of the leading branches of research which enables the large-scale scanning of various substances, and offers great potential for post-genomics to elucidate the genotype-phenotype connections. The present chapter is an account of current knowledge in this regard. It focuses on effects of salt stress unrevealed by proteomics tools. It comprises information on recent advances in proteomics, which could be a new opportunity to comprehend abiotic responses and categorize genes responsible for significant crop traits.